Kesuksesan Karier Ditinjau dari Persepsi Pengembangan Karier dan Komitmen Karier pada Pekerja Millennial - Putu Aninditha Veera Lakshmi; Sumaryono Sumaryono (Faculty of Psychology, Universitas Gadjah Mada, 2018)
Millennial workers are concerned to succeed in their career so they are willing to move from one organization to another to have successful career. Based on that, it is important for organization to help millennial workers through career development program. Moreover, career success can also be realized by the commitment of employees to their careers. This study was a quantitative study which aimed to determine career success according to perceptions of career development and career commitment. Respondents in this study were millennial workers who work in hospitality industry which were sampled by quota sampling method. Data analysis was done using multiple regression analysis and yielded F = 80.450; p < 0.01. The results of this study stated that perceptions of career development and career commitment are predictors of career success in millennial workers in hospitality industry. The influence of two two predictors contributed 44.8% in increasing career success.